WOOL PRODUCTIVITY OF LOCAL GOATS IN USTYURT CONDITIONS - Turganbayev Ruzimbai Urazbaevich; Kaniyazova Fatima Ubbiniyazovna (The Conference Hub, 2025)
This article examines the dependence of wool productivity in local goats on pasture areas under the conditions of the Ustyurt Plateau. The study identifies differences in wool productivity based on various pasture areas and presents relevant conclusions.
Keywords: Ustyurt Plateau, local goats, wool productivity, pasture areas, conclusions.